2021
DOI: 10.31234/osf.io/hqgz7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Where the genome meets the connectome: understanding how genes shape human brain connectivity

Abstract: The integration of modern neuroimaging methods with genetically informative designs and data can shed light on the molecular mechanisms underlying the structural and functional organisation of the human connectome. Here, we review studies that have investigated the genetic basis of human brain network structure and function through three complementary frameworks: (1) the quantification of phenotypic heritability through classical twin designs; (2) the identification of specific DNA variants linked to phenotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 196 publications
0
10
0
Order By: Relevance
“…Firstly, we focused on the white matter microstructure in this study because anatomical measures are reported to be more closely related to genetic factors than functional connectivity. 84 At the time of the writing of this paper, there is no clear meta-analytic evidence of common functional alterations across individuals with ADHD. 85 , 86 In the future, other types of imaging data like functional MRI may be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we focused on the white matter microstructure in this study because anatomical measures are reported to be more closely related to genetic factors than functional connectivity. 84 At the time of the writing of this paper, there is no clear meta-analytic evidence of common functional alterations across individuals with ADHD. 85 , 86 In the future, other types of imaging data like functional MRI may be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of the study include our reliance on gene expression maps from postmortem examination of six adult, mostly male, brains. This dataset is used widely and has been invaluable in shedding new light on the molecular correlates of neuroimaging phenotypes ( 77 ). Biological validation of sexually divergent adolescent development of this cortico-subcortical system derived from fMRI would be more directly informed by sex-specific human brain maps of whole-genome transcription in adolescence, but to the best of our knowledge, these data are not currently available.…”
Section: Discussionmentioning
confidence: 99%
“…While both neuroimaging and genetic studies each have pointed to synaptic alterations in psychiatric disorders, only a few have specifically tested this hypothesis in an integrated imaging-genetics framework. A few studies have explored the genetic architecture of functional brain connectivity 1923 , and studies assessing polygenic risk scores have indicated links between psychiatric disorders and abnormal brain connectivity 24,25 . Previous studies also illustrated genetic correlation between various brain imaging phenotypes and psychiatric disorders that confirm a large degree of shared effect sizes across single nucleotide polymorphisms (SNPs) 2628 .…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have explored the genetic architecture of functional brain connectivity [19][20][21][22][23] , and studies assessing polygenic risk scores have indicated links between psychiatric disorders and abnormal brain connectivity 24,25 . Previous studies also illustrated genetic correlation between various brain imaging phenotypes and psychiatric disorders that confirm a large degree of shared effect sizes across single nucleotide polymorphisms (SNPs) [26][27][28] .…”
Section: Introductionmentioning
confidence: 99%